Probing the functional constraints of influenza A virus NEP by deep mutational scanning - Qi Wen Teo; Yiquan Wang; Huibin Lv; Michael S. Oade; Kevin J. Mao; Timothy J.C. Tan; Yang Wei Huan; Joel Rivera-Cardona; Evan K. Shao; Danbi Choi; Chaoyang Wang; Zahra Tavakoli Dargani; et al. (Cell Reports)
Summary: The influenza A virus nuclear export protein (NEP) is a multifunctional protein that is essential for the viral life cycle and has very high sequence conservation. However, since the open reading frame of NEP largely overlaps with that of another influenza viral protein, non-structural protein 1, it is difficult to infer the functional constraints of NEP based on sequence conservation analysis. In addition, the N-terminal of NEP is structurally disordered, which further complicates the understanding of its function. Here, we systematically measure the replication fitness effects of >1,800 mutations of NEP. Our results show that the N-terminal domain has high mutational tolerance. Additional experiments show that N-terminal domain mutations affect viral transcription and replication dynamics, host cellular responses, and mammalian adaptation of avian influenza virus. Overall, our study not only advances the functional understanding of NEP but also provides insights into its evolutionary constraints.